Penerapan Model Pembelajaran SAVI terhadap Kemampuan Representasi Matematis Siswa Kelas VIII SMP Darudda’wah Punggur Kecil - Aprilyani, Safitri; Siti Nur Asma; Metia Novianti (JURNAL ARMADA PENDIDIKAN, 2024)
This study aims to describe the application of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on students’ mathematical representation abilities especially on the Pythagorean Theorem theme, using a quantitative approach. The type of this research is descriptive. In this type of research, there is only one group that will receive treatment, which involves being taught using the SAVI learning model. The study concludes that the SAVI learning model has been proven effective in improving students’ mathematical representation abilities. The research shows a significant improvement in students’ learning outcomes after the implementation of this model. Before the application of the SAVI model, the average student score was 25.89. After the implementation, the average student score increased to 65.89. This increase indicates that the SAVI model effectively enhances students’ understanding and mathematical skills. The implementation of this model shows a significant improvement in students’ average scores, from 25.89 before the implementation, to 65.89 after the implementation. The calculation of the N-Gain score also confirms a positive increase in students’ mathematical abilities. Thus, the SAVI model not only improves academic results but also enhances the overall quality of mathematics education, making it a valuable method for application in mathematics education practices.